Endoscopic submucosal dissection for duodenal tumors: a single-center experience - Matsumoto, S.; Miyatani, H.; Yoshida, Y. (Endoscopy, 2013)
The indications for endoscopic submucosal dissection (ESD) for duodenal tumors have not yet been established. We reviewed our experience of ESD performed for duodenal tumors. We analyzed the data of a total of 13 patients with 14 duodenal lesions (excluding papillary lesions) comprising 2 early cancers, 5 adenomas, and 7 neuroendocrine tumors, who were treated by ESD between 2005 and 2011. The mean tumor diameter was 12.7 ± 14.8 mm. En bloc resection was achieved in 85.7 % of the cases. The procedure time was 89.1 ± 64.6 minutes. Intraoperative perforation occurred in three cases. The mean length of postoperative hospitalization was 8.4 ± 2.4 days. Because ESD for duodenal lesions was associated with a higher incidence of perforation than ESD for lesions in other locations (stomach, esophagus, and colon) reported previously, its use for duodenal lesions should be considered with caution.